Protein kinase G signaling in cardiac pathophysiology: Impact of proteomics on clinical trials. Issue 5 (16th February 2016) - Kirk, Jonathan A.; Holewinski, Ronald J.; Crowgey, Erin L.; Van Eyk, Jennifer E.
Abstract : The protective role of cyclic guanosine monophosphate (cGMP)‐stimulated protein kinase G (PKG) in the heart makes it an attractive target for therapeutic drug development to treat a variety of cardiac diseases. Phosphodiesterases degrade cGMP, thus phosphodiesterase inhibitors that can increase PKG are of translational interest and the subject of ongoing human trials. PKG signaling is complex, however, and understanding its downstream phosphorylation targets and upstream regulation are necessary steps toward safe and efficacious drug development. Proteomic technologies have paved the way for assays that allow us to peer broadly into signaling minutia, including protein quantity changes and phosphorylation events. However, there are persistent challenges to the proteomic study of PKG, such as the impact of the expression of different PKG isoforms, changes in its localization within the cell, and alterations caused by oxidative stress. PKG signaling is also dependent upon sex and potentially the genetic and epigenetic background of the individual. Thus, the rigorous application of proteomics to the field will be necessary to address how these effectors can alter PKG signaling and interfere with pharmacological interventions. This review will summarize PKG signaling, how it is being targeted clinically, and the proteomic challenges and techniques that are being used to study it.